Review of empirical studies in HPM2004 & ESU4: Empirical research in the field of using history in mathematics education - Jankvist, Uffe Thomas (NOMAD Nordic Studies in Mathematics Education, 2007)
This paper discusses empirical studies in the proceedings HPM2004 & ESU4. More precisely the paper deals with four of the more clear-cut empirical studies. These are the contributions by B. Smestad, C. Tzanakis & M. Kourkoulos, W.-S. Horng, and Y.-W. Su. These contributions are first presented and then later discussed in the context of whether their purpose of involving the history of mathematics in mathematics education is to promote the learning of mathematics or if it is to bring about aspects of mathematics which are not normally part of the teaching and learning agenda, e.g. cultural or social aspects of mathematics and its history – ’history as a tool’ or ’history as a goal’. The papers and their purposes for involving history are then related to a Nordic case, namely the official regulations for the Danish upper secondary mathematics programme for involving the history of mathematics. In the end the need for empirical research studies in the field of using history in mathematics education is discussed as well as further perspectives for the community regarding such studies or the lack of them.